2012
DOI: 10.1111/j.1752-8062.2012.00424.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model for Fetal Maternal Stem Cell Transfer during Ischemic Cardiac Injury

Abstract: Fetal cells enter the maternal circulation during pregnancies and can persist in blood and tissues for decades, creating a state of physiologic microchimerism. Microchimerism refers to acquisition of cells from another individual and can be due to bi-directional cell traffic between mother and fetus during pregnancy. Peripartum cardiomyopathy, a rare cardiac disorder associated with high mortality rates has the highest recovery rate amongst all etiologies of heart failure although the reason is unknown. Collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…FMc has been mainly studied in humans, rodents, and rhesus monkeys ( Jimenez and Tarantal 2003a , 2003b ; Jimenez et al., 2005 ; Khosrotehrani et al., 2005 ). Feto-maternal cell trafficking has been described to start between the fourth and sixth week of gestation in humans ( Ariga et al., 2001 ), the 11th day in rodents ( Yutaka et al.,2009 ) and the fourth week in rhesus monkeys and increases exponentially throughout the gestational period, reaching its maximum level in the days before childbirth ( Jimenez and Tarantal 2003a , 2003b ; Jimenez et al., 2005 ; Kara et al., 2012 ; Klonisch and Drouin 2009 ; Vernochet et al., 2007 ). Most fetal cells gradually disappear from the blood circulation during the first weeks post-gestation ( Kolialexi et al., 2004 ; Jimenez and Tarantal 2003a , 2003b ; Jimenez et al., 2005 ; Ariga et al., 2001 ; Lambert and Nelson, 2003 ; Nelson, 2002a , 2002b ), being eliminated by the maternal immune system ( Kolialexi et al., 2004 ; Ariga et al., 2001 ; Srivatsa et al., 2001 ).…”
Section: Detection and Characterization Of Fmc In Animal And Human Maternal Tissuesmentioning
confidence: 99%
“…FMc has been mainly studied in humans, rodents, and rhesus monkeys ( Jimenez and Tarantal 2003a , 2003b ; Jimenez et al., 2005 ; Khosrotehrani et al., 2005 ). Feto-maternal cell trafficking has been described to start between the fourth and sixth week of gestation in humans ( Ariga et al., 2001 ), the 11th day in rodents ( Yutaka et al.,2009 ) and the fourth week in rhesus monkeys and increases exponentially throughout the gestational period, reaching its maximum level in the days before childbirth ( Jimenez and Tarantal 2003a , 2003b ; Jimenez et al., 2005 ; Kara et al., 2012 ; Klonisch and Drouin 2009 ; Vernochet et al., 2007 ). Most fetal cells gradually disappear from the blood circulation during the first weeks post-gestation ( Kolialexi et al., 2004 ; Jimenez and Tarantal 2003a , 2003b ; Jimenez et al., 2005 ; Ariga et al., 2001 ; Lambert and Nelson, 2003 ; Nelson, 2002a , 2002b ), being eliminated by the maternal immune system ( Kolialexi et al., 2004 ; Ariga et al., 2001 ; Srivatsa et al., 2001 ).…”
Section: Detection and Characterization Of Fmc In Animal And Human Maternal Tissuesmentioning
confidence: 99%
“…Studies have documented that fetal cells primarily populate the bone marrow (which is activated by stroke via the sympathetic nervous system), and that these cells can mobilize into circulation and enter target tissues in various animal models of cardiac, hepatic, renal, epidermal, and brain injury (45)(46)(47). Kara et al showed that MCs in a mouse model of myocardial infarction selectively home to the injured myocardium and differentiate into a variety of reparative cell types that were functional in vitro (48,49). Thus, the parous female bone marrow may house an endogenous population of stem cells of fetal origin that can potentially provide regenerative support.…”
Section: Discussionmentioning
confidence: 99%
“…Mice are a common model of human disease and have demonstrated pregnancy‐related chimerism similar to humans (Khosrotehrani et al, 2005; Perlman, 2016). Many studies have investigated the presence of persistent fetal cells in the non‐transgenic mother by enhanced green fluorescent protein models for detection (Kara et al, 2012). Both maternal and fetal chimerisms commonly occur in mice with detection in the tissues of all major organs (Khosrotehrani et al, 2005; Su, Johnson, Tighiouart, & Bianchi, 2008).…”
Section: Animal Studiesmentioning
confidence: 99%
“…Both maternal and fetal chimerisms commonly occur in mice with detection in the tissues of all major organs (Khosrotehrani et al, 2005; Su, Johnson, Tighiouart, & Bianchi, 2008). Studies of myocardial injury in pregnant mice have provided evidence of fetal cell migration to sites of cardiac injury and capacity for cardiac differentiation (Kara et al, 2012; Kara, Bolli, Matsunaga, et al, 2012). Fetal microchimerism in the lungs and brain of mice feature various cell types and have greater detection at the site of tissue injury from smoking or excitotoxic lesions, respectively, suggesting a potential protective effect (Pritchard, Wick, Slonim, Johnson, & Bianchi, 2012; Tan et al, 2005; Vogelgesang et al, 2014).…”
Section: Animal Studiesmentioning
confidence: 99%